A concentration inequality for the inverse Gaussian distribution: A tribute to the late Professor A. K. Md. E. Saleh (Journal of Statistical Research, 2025)
Concentration inequalities involving tail behavior of distributions have currently become very popular owing to their applications in the growing machine learning literature. The paper offers one such inequality for the less known, but equally important inverse Gaussian distribution.Journal of Statistical Research 2025, Vol. 59, No. 1, pp. 5-8